Analisa Perancangan Chicken Roaster - Galfri Siswandi; Petrisly Perkasa; Debora Debora; Pijai Pijai; Aldi Wira Prajoga (Jurnal Ilmiah Kanderang Tingang, 2022)
The chicken roaster has a function for roasting, by utilizing air for cooking it is considered more energy efficient than using charcoal completely. In the process, the charcoal used has weaknesses, such as the smoke produced and the preparation time is quite long. In addition, the food also becomes less hygienic and easy to burn. To overcome this, through community service activities, it is realized by making grills that are faster and easier by utilizing used waste. In the design, analysis is carried out to find out how far the usefulness of the tool according to the user. From the results of the questionnaire obtained three variables, namely the safety features of the tool and the ease of following the instructions for use which have a high index of 97%. For the next variable followed by tool design and color composition by 94%.